The effects of velocity on peak torque and neuromuscular responses during eccentric muscle actions - Hill, E. C.; Housha, T. J.; Camic, C. L.; Jenkins, N. D. M.; Smith, C. M.; Cochrane, K. C.; Cramer, J. T.; Schmidt, R. J.; Monaghan, M. M.; Johnson, G. O. (Isokinetics and Exercise Science, 2016)
BACKGROUND: Previous investigations have examined the torque and neuromuscular responses to maximal concentric and isometric muscle actions. The literature, however, has paid less attention to the effects of performing maximal eccentric muscle actions. Furthermore, the available information in this regard is contradictory. OBJECTIVE: The purpose of the present investigation was to examine eccentric, isokinetic peak moment (PMe), electromyographic (EMG) amplitude (AMP), EMG mean power frequency (MPF), mechanomyographic (MMG) AMP, and MMG MPF patterns of responses to repeated, maximal, eccentric muscle actions at 60, 120, and 180°/s. METHODS: Twelve resistance-trained men visited the laboratory on three occasions (separated by = 72 h) and performed 30 repeated, maximal, eccentric muscle actions of the dominant leg extensors on an isokinetic dynamometer at randomly ordered velocities of 60, 120, and 180°/s. RESULTS: There were no changes (p > 0.05) across the 30 repeated, eccentric muscle actions for PMe, MMG AMP, and EMG MPF for any of the velocities. There were, however, increases in EMG AMP and decreases in MMG MPF for each velocity. CONCLUSIONS: The decrease in MMG MPF, which reflects the global firing rate of the activated motor units, in conjunction with the lack of change in MMG AMP, which reflects motor unit recruitment, suggested that the increase in EMG AMP was due to motor unit synchronization. ABSTRACT FROM AUTHOR